2015
DOI: 10.1136/thoraxjnl-2014-205914
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical effectiveness of first-line chemotherapy for adult patients with locally advanced or metastatic non-small cell lung cancer

Abstract: Our aim was to evaluate the clinical effectiveness of chemotherapy treatments currently licensed in Europe and recommended by the National Institute for Health and Care Excellence (NICE) for the first-line treatment of adult patients with locally advanced or metastatic non-small cell lung cancer (NSCLC). A systematic search of MEDLINE, EMBASE and the Cochrane Library for randomised controlled trials (RCTs) published from 2001 to 2010 was carried out. Relative treatment effects for overall survival (OS) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 38 publications
(172 reference statements)
2
74
1
Order By: Relevance
“…Although surgical resection, radiotherapy and chemotherapy have led to improvements in the treatment of NSCLC, the prognosis of patients remains poor (1,2). Therefore, development of effective therapeutic targets for the treatment of NSCLC is required.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgical resection, radiotherapy and chemotherapy have led to improvements in the treatment of NSCLC, the prognosis of patients remains poor (1,2). Therefore, development of effective therapeutic targets for the treatment of NSCLC is required.…”
Section: Introductionmentioning
confidence: 99%
“…That hypothesis-generating outcome is consistent with the recent meta-analysis by Sahgal et al 9 , in which improved survival was observed for patients less than 50 years of age treated with srs alone compared with those treated with upfront wbrt. One hypothesis that those findings support is that, by limiting the acute toxicity of wbrt, patients and oncologists are more likely to pursue palliative chemotherapy, which could ultimately influence a patient's os 11,17 .…”
Section: Discussionmentioning
confidence: 80%
“…2 Unfortunately, the use of traditional chemotherapy drug is limited by its unsatisfactory efficacy, poor selectivity, high drug resistance and toxicity to normal tissue. 3 Therefore, it is necessary to develop novel drug formulations with high efficacy but low toxicity.…”
Section: Introductionmentioning
confidence: 99%